Eliminating Tobacco Disparities Among Native Hawaiian Pacific Islanders Through Policy Change: The Role of Community-Based Organizations. Issue 5 (September 2013) - Palmer, Paula Healani; Lee, Cevadne; Sablan-Santos, Lola; Lepule, Jonathan Tana; Pang, Victor Kaiwi; Tui'one, Vanessa; Schmidt-Vaivao, Dorothy; Sabado, Melanie Dee; Sur, Roger; Tanjasiri, Sora P.
Although cigarette smoking in the general U.S. population has decreased considerably over the past several decades, prevalence rates among Native Hawaiian Pacific Islanders (NHPI) have remained elevated by comparison with other groups. The aggregation of NHPI smoking data with that of Asians has drawn attention away from the serious smoking problems that NHPIs experience, thus, limiting funding, programs, and policies to reduce tobacco-related health disparities in their communities. In California, community-based organizations (CBOs) have played a major role in supporting the state's comprehensive tobacco control program, which is arguably one of the most successful in the nation. In this commentary, we describe the tobacco control activities of five NHPI-serving CBOs in Southern California and how they have provided anti-tobacco education for thousands of Native Hawaiians, Chamorros, Marshallese, Samoans, Tongans, and other Pacific Islander subgroups, and used advocacy and coalition building to promote smoke-free environment policies in their communities. The concerted efforts of the CBOs and their community members have made vital contributions to the reduction of tobacco-related disparities for NHPI populations in California.